A new structure family of oxide-ion conductors Ca0.8Y2.4Sn0.8O6 discovered by a combined technique of the bond-valence method and experiments. Issue 22 (23rd May 2018) - Inoue, Ryota; Fujii, Kotaro; Shiraiwa, Masahiro; Niwa, Eiki; Yashima, Masatomo
Abstract : Mg3 TeO6 -type Ca0.8 Y2.4 Sn0.8 O6 was found as a new structure family of oxide-ion conductors by BVE calculations followed by experiments. Abstract : Mg3 TeO6 -type Ca0.8 Y2.4 Sn0.8 O6 has been found as a new structure family of oxide-ion conductors. From bond-valence-based energy (BVE) calculations for 147 compositions, which contain tin (Sn) as an essential element, Mg3 TeO6 -type Ca0.8 Y2.4 Sn0.8 O6 was found to have a low energy barrier for oxide-ion migration. Ca0.8 Y2.4 Sn0.8 O6 was synthesized by the solid-state reaction, and its electrical conductivity and crystal structure were investigated. The total electrical conductivity at various partial oxygen pressures and band gap estimated from the UV-vis spectrum suggested that Ca0.8 Y2.4 Sn0.8 O6 is a pure oxide-ion conductor. The activation energy for the oxide-ion conductivity of Ca0.8 Y2.4 Sn0.8 O6 was 1.39(4) eV. Synchrotron X-ray powder diffraction data of Ca0.8 Y2.4 Sn0.8 O6 at 300 and 1273 K were successfully analyzed with the Mg3 TeO6 -type structure. The BVE calculation using the refined crystal structure of Ca0.8 Y2.4 Sn0.8 O6 at 1273 K strongly suggested three dimensional oxide-ion diffusion.